Both better and worse than others depending on difficulty: Replication and extensions of Kruger’s (1999) above and below average effects - Max Korbmacher; Ching (Isabelle) Kwan; Gilad Feldman (Judgment and Decision Making, 2022)
Above-and-below-average effects are well-known phenomena that arise when comparing oneself to others. Kruger (1999) found that people rate themselves as above average for easy abilities and below average for difficult abilities. We conducted a successful pre-registered replication of Kruger’s (1999) Study 1, the first demonstration of the core phenomenon (N = 756, US MTurk workers). Extending the replication to also include a between-subject design, we added two conditions manipulating easy and difficult interpretations of the original ability domains, and with an additional dependent variable measuring perceived difficulty. We observed an above-average-effect in the easy extension and below-average-effect in the difficult extension, compared to the neutral replication condition. Both extension conditions were perceived as less ambiguous than the original neutral condition. Overall, we conclude strong empirical support for Kruger’s above-and-below-average effects, with boundary conditions laid out in the extensions expanding both generalizability and robustness of the phenomenon.